2007
DOI: 10.1007/s11664-007-0259-5
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Activation of Shallow Dopants Implanted in Silicon

Abstract: Dopant impurities were implanted at high dose and low energy (10 15 cm -2 , 0.5-2.2 keV) into double-side polished 200 mm diameter silicon wafers and electrically activated to form p-n junctions by 10 s anneals at temperatures of 1,025, 1,050, and 1,075°C by optical heating with tungsten incandescent lamps. Activation was studied for P, As, B, and BF 2 species implanted on one wafer side and for P and BF 2 implanted on both sides of the wafer. Measurements included electrical sheet resistance (Rs) and oxide fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Some laboratories examined the electrical activation of implanted dopants (which is loosely related to diffusion), but observed similar variability in the results. 8 Better progress has been made for surface diffusion, where experiments that fully decoupled heating from illumination showed that low-level photostimulation can affect the diffusion of adsorbed Ge and In on Si(111) by nearly an order of magnitude. 9,10 The experiments also showed clear correlation between doping type and diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Some laboratories examined the electrical activation of implanted dopants (which is loosely related to diffusion), but observed similar variability in the results. 8 Better progress has been made for surface diffusion, where experiments that fully decoupled heating from illumination showed that low-level photostimulation can affect the diffusion of adsorbed Ge and In on Si(111) by nearly an order of magnitude. 9,10 The experiments also showed clear correlation between doping type and diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Because the athermal component of annealing is less than about 10-20% of the thermal component, from an experimental point of view, it is quite challenging to design the experiment where the light component is completely separated from the thermal component of annealing. For example, Fiory [4] used wafers implanted on both sides and stacked with a second light shielding wafer. The problem with this type of experiment is that the temperature and energy of incident photons of exposed and shielded surface differs significantly.…”
Section: Introductionmentioning
confidence: 99%
“…1 The optical stimulation was long thought to supply heating alone, although scattered experimental evidence had hinted at additional nonthermal influences on diffusion and activation of phosphorous, 2 arsenic, [3][4][5] and boron. 4,[6][7][8] However, the experiments were difficult to interpret reliably because lamps supplied the heating, thereby complicating the decoupling of heating and photostimulation effects. Some progress was achieved in quantifying photoenhanced diffusion in II-VI semiconductors (using computational methods) 9 and a-Si:H (experimentally), 10 yet the understanding of the photostimulated dopant diffusion in c-Si remained inadequate.…”
mentioning
confidence: 99%